Euro-Asian Transport Corridors and the Eurasian Economic Union - E. T. Mekhdiev (Международная аналитика, 2018)
The article deals with international transport corridors linking Asia and Europe both through the territory of the EEU, and bypassing the Union. The author analyzes the advantages and disadvantages of existing and emerging routes, taking into account the interests of Russia. A special attention is paid to China and its initiatives in the transport and logistics sphere. In conclusion, the author notes that ensuring the attractiveness of the Euro-Asian transport corridors passing through the territory of the EEU requires a set of measures aimed at creating favorable conditions for transit.